Malaysian Halal Standard (Ms1500:2004) : Do Halal Food Manufacturers Have Intention To Be Certified ? - S.M.Mohiyaddin, Mohamad Ijaz (2006)

(untitled)
The Malaysian government has a vision of becoming a global halal hub. In line with this MS 1500:2004 Halal Standard was introduced as extension to the existing halal logo and certification. The objective of this study is to investigate whether there is any intention of halal food manufacturers to be certified with the Halal Standard.